Paul Collier. The Future of Capitalism: Facing the New Anxieties. London, UK: Allen Lane. 2018. 256 pages. Price UK £ 20.00 (Hardback). (The Pakistan Development Review, 2018)
The Future of Capitalism by Paul Collier is an insightful book. In this book the author has highlighted the things that are wrong with capitalism. He has also highlighted not only the problems created by capitalism but also the problems being faced by capitalism today. The author has made a cogent case to show that deep economic rifts in the UK and the USA are “tearing apart the fabric of our societies” (p. 3). Collier has, in a nutshell, shown in the book how to save the capitalism from itself. The book is different from the books written with either the conservative or with the liberal perspective in that rather than relying on mere rhetoric, Collier has tried to present pragmatic solutions to the socioeconomic problems that are so rampant today. He has argued that in these times when there are deep political divisions, no new economic theory can work the magic. Instead he has made a case for policies that are not only pragmatic but are communitarian in nature. What is unique about the book is that ethics and moral philosophy are at the centre stage of Collier’s narrative. George Akerloff, a Nobel laureate in Economics, has termed the book as the most revolutionary work since Keynes.